History in the making the heritage of the Assemblies of God - Assemblies of God. General Council; Wood, George; Nene, Jeff.; Harris, Steve; Flower Pentecostal Heritage Center ([Springfield, Mo.] : Assemblies of God, 1999)
A video window into the Assemblies of God, capturing the historical move of the Holy Spirit and featuring its current ministries and outreaches.
DVD.
"Presentation of the Flower Pentecostal Heritage Center"--Container.
Editor, Jim Ellenwood ; videographers, Todd Trask, Joe Mason, Frank Gamble, Jeff Nene.
"750-195."
Keywords: Assemblies of God; Assemblies of God -- History; Pentecostalism -- 20th century